KO SE SMATRA ASHABOM - Asad, Muhammed; Maljoki, Fadilj (Novi Muallim, 2022)
UDK 28-312-55 28-725-4/-5 Uvodne napomene u poglavlju/knjizi “Vrline ashaba”, u: Muhammad Asad, Saḥīḥ Al-Buhārī: The Early Years of Islam, Dar Al-Andalus, Gibraltar, 1993., str. 13 – 16. Prijevod i uvodna bilješka: Fadilj Maljoki